Tinjauan Komparatif Game-Based Learning berbasis Media Ludo untuk Penguatan Pendidikan Karakter dan Kecakapan Abad 21 dalam Pembelajaran Bahasa Arab - Syafira Risti Sinatrya; Khaerudin Khaerudin; Cecep Kustandi; Imam Fitri Rahmadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Strengthening 21st century character and skill education is an important demand in today's learning transformation. Game-Based Learning (GBL)-based approaches such as Ludo are believed to present a learning process that is meaningful, fun, while forming positive values. This study aims to review and compare the results of previous studies on the application of GBL in the development of character and skills in the 21st century, especially in Arabic language learning. The method used is a simple systematic literature review of 12 scientific articles published in 2015–2025 obtained from selected scientific databases. The analysis was conducted based on three main dimensions: the game medium, the focus of learning (characters, 4Cs, vocabulary), and the method approach. The results of the study show that GBL is generally effective in improving vocabulary mastery and fostering collaboration, communication, and character values of students. Ludo media in particular has proven to be relevant as a means of value-based learning and interaction. However, studies that explicitly integrate Ludo-based GBL in Arabic language learning are still limited. This research is expected to be a conceptual basis for the development of innovative learning media that is integrative and in accordance with the challenges of 21st century education.